2009
DOI: 10.1073/pnas.0812076106
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for specific recognition of multiple mRNA targets by a PUF regulatory protein

Abstract: Caenorhabditis elegans fem-3 binding factor (FBF) is a founding member of the PUMILIO/FBF (PUF) family of mRNA regulatory proteins. It regulates multiple mRNAs critical for stem cell maintenance and germline development. Here, we report crystal structures of FBF in complex with 6 different 9-nt RNA sequences, including elements from 4 natural mRNAs. These structures reveal that FBF binds to conserved bases at positions 1-3 and 7-8. The key specificity determinant of FBF vs. other PUF proteins lies in positions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(166 citation statements)
references
References 43 publications
6
160
0
Order By: Relevance
“…However, alanine substitutions in the stacking residues of repeats 1 and 5, as well as in the edge-on residues of repeats 1, 4, 5 and 8, allowed 10% or more β-gal activity. These data are consistent with interactions in the crystal structures of FBF-2/RNA complexes (30).…”
Section: Systematic Mutagenesis Reveals a Common Pattern Of Recognitionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, alanine substitutions in the stacking residues of repeats 1 and 5, as well as in the edge-on residues of repeats 1, 4, 5 and 8, allowed 10% or more β-gal activity. These data are consistent with interactions in the crystal structures of FBF-2/RNA complexes (30).…”
Section: Systematic Mutagenesis Reveals a Common Pattern Of Recognitionsupporting
confidence: 79%
“…The identity of the base present in each mutant is indicated immediately below the bars; the identity in WT is indicated below that. Amino acid side chains and bases in the FBF-2/FBE (C), Puf4p/4BE (F), and Puf3p/3BE (I) complexes are derived from the crystal structures (29,30,35). Green amino acid chains allowed ≥10% β-gal when mutated to alanine, and red side chains allowed <10% when mutated to alanine.…”
Section: Systematic Mutagenesis Reveals a Common Pattern Of Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although biochemical and structural studies of PUFs have shown that they interact with RNA in a modular manner, their diverse repeats make designing RNA-binding proteins free from context-dependent effects or with predictable binding affinities challenging. Furthermore, the structures of PUF proteins provide certain key limitations to their possible applications; their overall fold limits the number of repeats that can be assembled contiguously and the tendency for some bases of the target RNA to flip out from the RNA-binding surface can result in reduced RNA-binding specificity [35][36][37][38] . PPR proteins have a number of desirable features that make the development of their applications in biotechnology and synthetic biology quite appealing, now that a robust soluble and fully synthetic PPR module has been developed.…”
Section: Discussionmentioning
confidence: 99%
“…23 The basis for this selectivity lies in the nucleotides at positions 4-6 of the target mRNA. 35 Further complicating the issue, Puf proteins can act alone or in combination with other Puf proteins or protein partners to recognize their target RNAs. 9,36-38…”
Section: Target Rnas For Pumilio Proteinsmentioning
confidence: 99%